3 SPECT/CT quantification of DPD scintigraphy in cardiac amyloid. (May 2018) - Scully, PR; Morris, E; Burniston, M; Treibel, TA; Jerrum, M; Bedford, K; Queenan, H; Hartman, N; Mullen, M; Ozkor, M; Kennon, S; Newton, J; et al.
Abstract : Introduction: 99m Tc-3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) scintigraphy offers a sensitive, non-invasive test for cardiac transthyretin amyloid. The Perugini grading system relies on a visual score of the planar image – from grade 0 (negative) to 3 (strongly positive). SPECT allows the 3D visualisation of radioactivity within the body. SPECT/CT quantification may improve diagnostic accuracy and offer a means of measuring amyloid burden. Methods: The software algorithm (Hermes Medical) converts recorded counts per voxel into activity per unit volume, enabling quantitative reconstructions and display of standardised uptake values (SUV). Volumes of interest were placed over the heart, adjacent vertebra, paraspinal muscle and liver and peak SUV (SUVpeak ) recorded. P -values were calculated using a one-way ANOVA. Results: We identified 32 patients (aged 82±9 years, 59% male), with a range of DPD results (10 grade 0, 6 grade 1, 12 grade 2, 4 grade 3). Cardiac SUVpeak increased from Perugini grade 0 to 2, but plateaued at 3 (1.39±0.47 vs 3.82±1.66 vs 12.89±4.39 vs 10.79±1.12; p<0.001). Vertebral SUVpeak decreased from Perugini grade 0 to 3 (11.75±3.79 vs 9.60±2.28 vs 8.34±2.25 vs 5.85±1.53; p<0.006). Paraspinal muscle SUVpeak increased from Perugini grade 0 to 3 (0.50±0.13 vs 0.57±0.13 vs 0.76±0.27 vs 1.29±0.24; p<0.001). Liver SUVpeak did not vary between grades (p=0.952). On ROC analysis, a cardiac SUVpeak of 2.3 diagnosed amyloidosis with 95% sensitivity and 90% specificity. Conclusion: SPECT/CT quantification in DPD scintigraphy has diagnostic and discriminatory power. Competition for tracer between skeletal muscle and the heart in grade 3 cases may confound quantification of cardiac amyloid burden.